Edukasi Duduk Ergonomi dan Latihan Metode Scroth pada Kasus Scoliosis di SMP Nurul Ilmi Jambi - Sari, Indah Permata; Hadi, Putra (Universitas Baiturrahim, 2025)
Scoliosis is a posture disorder caused by changes in the shape and function of the muscles and bones in the vertebrae. Postural changes are seen in the frontal plane, namely the presence of a lateral curve associated with sagittal and transverse rotation. The Schroth method is a form of physiotherapy for scoliosis, which is a conservative treatment, which is based on the principles of specific postural correction, correction of breathing pattern and correction of postural perception. The aim of the Schroth method is to correct the spine in the sagittal, frontal and transverse planes. The aim of this community service education is to increase the knowledge of Nurul Ilmi Middle School students about the correct sitting position in cases of scoliosis. Method of implementing educational activities using lecture, demonstration and question and answer methods with a total of 30 participants. The material presented is about the correct sitting position, how to define scoliosis, causes, prevention, and scoliosis exercises. To determine participants' understanding of the material presented, an evaluation was carried out using a questionnaire. The results of this community service activity show an increase in junior high school students' knowledge and understanding regarding the correct sitting position in cases of scoliosis.